Flexible Ferroelectrics: Periodic Wrinkle‐Patterned Single‐Crystalline Ferroelectric Oxide Membranes with Enhanced Piezoelectricity (Adv. Mater. 50/2020). Issue 50 (15th December 2020) - Dong, Guohua; Li, Suzhi; Li, Tao; Wu, Haijun; Nan, Tianxiang; Wang, Xiaohua; Liu, Haixia; Cheng, Yuxin; Zhou, Yuqing; Qu, Wanbo; Zhao, Yifan; Peng, Bin; et al.
Abstract : In article number 2004477, Ziyao Zhou, Xiangdong Ding, Tai Min, Ming Liu, and co‐workers present a periodically wrinkled structure that combines flexible ferroelectric membranes and organic elastomers. Enhanced piezoelectricity is observed at the sites of the peaks and valleys of the wrinkles where the largest strain gradient is generated. The wrinkle‐patterned ferroelectric membranes offer an ideal platform to explore the periodic‐electric‐potential‐induced functions in flexible electrical and optical devices.